An exploratory study of the best dispute resolution in strata management - Mohamad, Nor Asiah; Sufian, Azlinor (2017)
Strata titles are important to evidence ownership. Living in strata properties involves communal responsibilities and sharing common facilities that are known as common properties. In this situation, it is nonetheless predictable that there are bound to be disagreements and disputes among the residents and the management body or residents and residents. Moreover, the trend of empowering purchaser-owners to manage their own properties and the common properties has, to an extent, created challenges in the administration of strata properties. This has resulted in the need for guidelines and laws to ensure smooth management of the properties. In relation to this, the Malaysian government is committed to do improvements from time to time in order to minimise problems faced by various parties in strata properties. It is evident that within more than 25 years since the first introduction of Strata Title Act 1985, there are three legislations that have been prepared and the Strata Titles Act 1985 has been implemented with a number of amendments. The statutes are; the Strata Titles Act 1985 (STA 1985), the Building and Common Property Act (management and maintenance) 2007 (BCPMMA 2007) and the Strata Management Act 2013 (Act 757) (SMA 2013) which was given the Royal Assent and gazetted on 5th February and 8th February 2013 respectively. In addition, management of the strata building; residential or commercial; are also monitored and controlled via other related laws such as the National Land Code 1965, the Housing Developer’s Act 1966 and the Contract Act 1950.